Akidah dan syariah Islam (al Islam aqidah wa syari'ah ) - Syeikh Mahmud Shaltut (Bumi Aksara, Bina Aksara, 1984)
Oen, Jil.1=c.1-7;Jil.2=c.1-9 / ir, jil.1,c.8 ; jil.2,c.10/tr, jil.1=c.10-12; jil.2=c.11-12/en, jil.1=c.13/en, jil.1=c.14